Enhancing the Reliability of Urea Pumps in Fertilizer Production Lines through Exponential Reliability Analysis - Johnson, Michael; Carter, Emily; Anderson , William (Ayden Journal of Engineering and Applied Sciences, 2024)
This research aimed at improving the reliability of the urea pump of a fertilizer production line at Urea Plant of Notore Chemical Industry Limited, Onne, Rivers State, Nigeria, using reliability exponential analysis.The investigation of the constraints associated with the performance of the fertilizer production line by analysis of maintenance log revealed that the pump was the most frequently failed critical component. Failure data of the urea pump, evaporator, scrubber and condenser were obtained from logged maintenance activities, which were used to carry out reliability analysis using exponential failure distribution model for a period of five years (2014 to 2018). Thereafter, triple redundancy was introduced to have enhance a balanced pressure and act as backup when failure occurs and consequently prevent breakdown. Also, a pressure monitors with an alarm system had been installed for immediate switchover to avoid sudden breakdown and equally reduce change over time prior to corrective maintenance. Results of reliability analysis carried out showed that reliability decreased from 64% to 30% from 2014 to 2018. However, after improvement strategies with redundant pumps, reliability for each year improved thus, 2014, 22%, 2015 35%, 2016, 36%, 2017, 35%, 2018, 34% respectively. This gives an average of 32.4% increase across the years. Conclusively, Preemptive maintenance strategy was adopted by planning maintenance schedule to coincide with idling time or shut down period to minimize losses from breakdown or corrective maintenance.